Negative Impact of Citral on Susceptibility of Pseudomonas aeruginosa to Antibiotics - Tetard, Alexandre; Foley, Sarah; Mislin, Gaëtan L. A.; Brunel, Jean-Michel; Oliva, Estefania; Torrealba Anzola, Freddy; Zedet, Andy; Cardey, Bruno; Pellequer, Yann; Ramseyer, Christophe; Plésiat, Patrick; Llanes, Catherine (Frontiers in Microbiology, 2021)
Essential oils (EOs) or their components are widely used by inhalation or nebulization to fight mild respiratory bacterial infections. However, their interaction with antibiotics is poorly known. In this study we evaluated the effects of citral, the main component of lemongrass oil, on in vitro susceptibility of Pseudomonas aeruginosa to antibiotics. Exposure of strain PA14 to subinhibitory concentrations of citral increased expression of operons encoding the multidrug efflux systems MexEF-OprN and MexXY/OprM, and bacterial resistance to anti-pseudomonal antibiotics including imipenem (2-fold), gentamicin (8-fold), tobramycin (8-fold), ciprofloxacin (2-fold), and colistin (≥128-fold). Use of pump deletion mutants showed that in addition to efflux other mechanisms were involved in this citral-induced phenotype. Determination of Zeta potential suggested that citral impairs the cell surface binding of aminoglycosides and colistin used at low concentrations (≤10 µg/mL). Moreover, experiments based on Raman spectroscopy and high-resolution mass spectrometry demonstrated formation of a Schiff base between the aldehyde group of citral and amino-groups of tobramycin and colistin. Chemical synthesis of tobracitryl, the imine compound resulting from condensation of citral and tobramycin, confirmed the loss of antibiotic activity due to adduct formation. Altogether these data point to the potential risk concern of self-medication with EOs containing citral in patients suffering from P. aeruginosa chronic lung infections and being treated with aerosols of aminoglycoside or colistin.